Fluorescence-based primary productivity estimates are influenced by non-photochemical quenching dynamics in Arctic phytoplankton - Sezginer, Yayla; Campbell, Douglas; Pillai, Sacchinandan; Tortell, Philippe (Frontiers in Microbiology, 2023)
Chlorophyll fluorescence-based estimates of primary productivity typically include dark or low-light pre-treatments to relax non-photochemical quenching (NPQ), a process that influences the relationship between PSII photochemistry and fluorescence yields. The time-scales of NPQ relaxation vary significantly between phytoplankton taxa and across environmental conditions, creating uncertainty in field-based productivity measurements derived from fluorescence. To address this practical challenge, we used fast repetition rate fluorometry to characterize NPQ relaxation kinetics in Arctic Ocean phytoplankton assemblages across a range of hydrographic regimes. Applying numerical fits to our data, we derived NPQ relaxation life times, and determined the relative contributions of various quenching components to the total NPQ signature across the different assemblages. Relaxation kinetics were best described as a combination of fast-, intermediate-and slow-relaxing processes, operating on time-scales of seconds, minutes, and hours, respectively. Across sampling locations and depths, total fluorescence quenching was dominated by the intermediate quenching component. Our results demonstrated an average NPQ relaxation life time of 20 ± 1.9 minutes, with faster relaxation among high light acclimated surface samples relative to lowlight acclimated sub-surface samples. We also used our results to examine the influence of NPQ relaxation on estimates of photosynthetic electron transport rates (ETR), testing the commonly held assumption that NPQ exerts proportional effects on light absorption (PSII functional absorption cross section, sPSII) and photochemical quantum efficiency (FV/FM). This assumption was violated in a number of phytoplankton assemblages that showed a significant decoupling of sPSII and FV/FM during NPQ relaxation, and an associated variability in ETR estimates. Decoupling of sPSII and FV/FM was most prevalent in samples displaying symptoms photoinhibition. Our results provide insights into the mechanisms and kinetics of NPQ in Arctic phytoplankton assemblages, with important implications for the use of FRRF to derive non-invasive, high-resolution estimates of photosynthetic activity in polar marine waters.